2020
DOI: 10.3390/ma13010191
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Effect of TDMs on the Tribological Behaviors of the Ionic Liquid Composite Films

Abstract: Ionic liquid (IL) combined with 2D materials has evoked considerable attention in the field of lubrication applications because of their speical structure and outstanding lubrication properties. However, the ambiguous effect of the 2D materials on the friction and anti-wear properties of the IL needs futher study. Here, we have obtained two families of IL composite films with additives of MoS 2 and graphene via a combined process of spin-coated and curing, and the distinction of the effects of two addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The analysis of the bonding between graphene and DLC shows that the amounts of covalent bonds between the interfaces increases significantly with the sliding velocity. This is because high sliding velocity induces the formation of wrinkles in the graphene, which can significantly drop the load-carrying capacity (critical value of graphene failure) by almost an order of magnitude [27]. Therefore, the graphene is more prone to rupture and resulting failure of lubrication at high V y .…”
Section: Friction Behaviors With Different Sliding Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the bonding between graphene and DLC shows that the amounts of covalent bonds between the interfaces increases significantly with the sliding velocity. This is because high sliding velocity induces the formation of wrinkles in the graphene, which can significantly drop the load-carrying capacity (critical value of graphene failure) by almost an order of magnitude [27]. Therefore, the graphene is more prone to rupture and resulting failure of lubrication at high V y .…”
Section: Friction Behaviors With Different Sliding Velocitymentioning
confidence: 99%
“…Functionalized multilayer graphene as additives can prominently enhance the anti-wear and friction-reducing ability of IL film under high vacuum, due to the lubrication synergy of ILs and multilayer graphene [26]. Qi et al found that the friction coefficient and anti-wear life were greatly improved with graphene as additives, ascribing to the improved load-carrying capacity and second lubricating phase [27]. Saurín et al found that the addition of monolayer graphene increases friction and wear rates due to the agglomerates of graphene in the epoxy resin-stainless steel interface, but they decrease with the addition of the same proportion of dispersed multilayer graphene [28].…”
Section: Introductionmentioning
confidence: 99%